KONSEP KONSUMSI DAN PERILAKU KONSUMSI ISLAM - JENITA JENITA; RUSTAM RUSTAM (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The research theme is the concept of business According to Islamic economics. Purpose of this study is to describe the concept of consumption and consumer behavior. Research is a research library. The results of the analysis and discussion that the concept of consumption and consumer behavior offered by Islam can realize the prosperity of society. The concept of consumption and consumer behavior in Islam put the principle such as beneficiaries and benefits.